The relationship between parental belief on filial piety and child psychosocial adjustment among Malay families - Ismail, Nellie; Tan, Jo Pei; Ibrahim, Rahimah (Universiti Putra Malaysia Press, 2009)
This study examines the relationship between parental belief on filial piety and child psychosocial adjustment among Malay families. The study sample comprised 108 mother-child dyads of Malay families from the central zone of Peninsular Malaysia. Data were collected using structured questionnaires. Parental belief was measured using Parental Belief Scale, while child psychosocial adjustment was measured using Strengths and Difficulties Questionnaire (SDQ). Results showed that children whose parents believed in filial piety had significantly lower levels of total difficulties in behavioural, emotional symptoms, conduct problem, and hyperactivity or inattention. Findings implied that filial piety could be used as a positive measure of behavioural and emotional control of a child. Therefore, it is important for parents to nurture their children about filial piety expectations so as to provide them with moral education associated with positive psychosocial adjustment.